THE REGULATION OF ANTI-COMPETETIVE BEHAVIOUR IN THE COMPETITION POLICY OF UZBEKISTAN: PROSPECTIVE - Sayokhat Akhrorova (Scholar Express Journals, 2023)
This article discusses the competitive environment in the Republic of Uzbekistan and some problems related to its legal regulation. The author's opinions are within the framework of national legislation, the identified shortcomings were compared with foreign experience, and an attempt was made to apply positive experiences to science. Certainly, opinions of a number of scientists, legal literature, legal documents and opinions of world organizations and they were studied and taken into account.
Keywords: ACRU; OECD; competition; monopoly